The Impact of Smoking Degree on One Year Survival of Non-Small Cell Lung Cancer (NSCLC) at Persahabatan Hospital - Wicaksono, Arief; Adisasmita, Asri C.; Putra, Andika Chandra (Jurnal Epidemiologi Kesehatan Indonesia, 2024)
Lung cancer is a major global mortality problem with the worst prognosis compared to other types of cancer. Non-small cell lung cancer (NSCLC) is the most common type of lung cancer and smoking is one of the main factors causing lung cancer. This study aims to determine the one-year survival of NSCLC patients with smoking levels and to determine what factors affect survival. This study is an observational study with a retrospective method, looking at medical record data of NSCLC patients both inpatients and outpatients at Persahabatan Hospital between January 2023 and December 2023 and then followed up until September 2024. Survival analysis using the Kaplan Meier method and the Log-Rank test was used to find the differences between variables. Based on 248 NSCLC patients, 105 patients had low-moderate degree of smoking, and 145 patients had severe degree of smoking. The average age are 57 years old. The highest level of education are high school/equivalent (178 patients). Employment status are workers (211 patients). Marital status are married (216 patients). Performance status are ECOG-PS >2 (137 patients). Clinical stage are stage IV (194 patients). The one-year survival probability was 28.13% in the low-moderate degree of smoking group and 39.82% in the severe degree of smoking group with a median 122 days and 234 days respectively. There was a statistically significant difference in survival probability between degree of smoking, employment status, marital status, performance status and clinical stage with p<0.05.